IDENTIFIKASI PRODUKTIVITAS TENAGA KERJA UNTUK OPTIMASI ANGGARAN BIAYA DALAM PELAKSANAAN PROYEK SKALA KECIL DI BALI: Labor Productivity Identification for Budget Cost Optimization in Small-Scale Project Implementation in Bali - Ida Ayu Cri, Vinantya Laksmi; Jawat, I Wayan; Dharmastika, I Gusti Agung Gede Nodya; Dewi, Ni Kadek Ayu Cipta; Putri, Komang Pipin Indraswari Berata (Universitas Negeri Surabaya, 2024)
The implementation of a construction project is highly dependent on the availability of labor which is the main driving force in the planning stage until the realization of the project. Without labor, it is impossible to achieve the goals of the project itself. The workability of the workforce is usually called productivity. One thing closely related to labor productivity is the cost of project implementation. The higher the productivity, the smaller the possibility of excess/inflation of project implementation costs, and vice versa. Based on this, further research is needed to determine the factors influencing labor productivity in implementing small-scale construction projects in Bali. Problem-solving and data analysis in this study used the Analytical Hierarchy Process (AHP) method. The results of the study showed that the most influential factors in labor productivity in project implementation were labor skills in carrying out work in the field (14.5%), equipment used during work (12.8%), the physical condition of workers (11.4%), job and work instructions given by superiors (11.3%), time schedule or work implementation time (10.5%), coordination between workers (10.2%), worker discipline during work or project implementation (10.1%), available materials (9.9%), and the last was the workspace or space available in carrying a job (9.4%).